Value Chain Analysis to Identify Internet of Things Use Cases in The Indonesian Pharmaceutical Industry - Wendy Junaidi (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2022)
The coronavirus pandemic has not only boosted the revenue of many pharmaceutical companies, it has also boosted their reputation. The value of pharmaceutical innovation is unquestionable, after the COVID-19 vaccine was developed at such a rapid pace. Besides, the coronavirus pandemic has exposed weakness in the industry's global supply chains and while consumer confidence is recovering, it is far from normal. Businesses in this sector are likely to face a number of major risks through the end of the year. The purpose of this study is to provide insights regarding challenges faced by the Indonesian pharmaceutical industry as driver to conduct value chain analysis in order to identify the prioritized internet of things use cases so pharmaceutical companies in Indonesia will be able to drive both top-line and operational efficiencies.